Pulse on pulse: modulation and signification in Rafael Lozano-Hemmer's Pulse Room - Merete Carlson (Journal of Aesthetics & Culture, 2012)
This article investigates the relation between signifying processes and non-signifying material dynamism in the installation Pulse Room (2006) by Mexican Canadian artist Rafael Lozano-Hemmer. In Pulse Room the sense of pulse is ambiguous. Biorhythms are transmitted from the pulsing energy of the visitor's beating heart to the flashing of a fragile light bulb, thereby transforming each light bulb into a register of individual life. But at the same time the flashing light bulbs together produce a chaotically flickering light environment composed by various layers of repetitive rhythms, a vibrant and pulsating “room”. Hence, the visitor in Pulse Room is invited into a complex scenario that continuously oscillates between various aspects of signification (the light bulbs representing individual lives; the pulse itself as the symbolic “rhythm of life”) and instants of pure material processuality (flickering light bulbs; polyrhythmic layers). Taking our point of departure in a discussion of Gilles Deleuze's concepts of modulation and signaletic material in relation to electronic media, we examine how the complex orchestration of pulsation between signification and material modulation produces a multilayered sense of time and space that is central to the sensory experience of Pulse Room as a whole. Pulse Room is, at the very same time, a relational subject–object intimacy and an all-encompassing immersive environment modulating continuously in real space-time.